Further Evidence of Organic Soft Hammer Percussion and Pressure Retouch from Lingjing (Xuchang, Henan, China). (3rd April 2019) - Doyon, Luc; Li, Hao; Li, ZhanYang; Wang, Hua; Zhao, QingPo
ABSTRACT: Opinions on the nature and distinctiveness of the Chinese Paleolithic differ between those who assign early Late Pleistocene lithic technologies to some peculiar facies of the Middle Paleolithic, and those who interpret them as reflecting the persistence of essentially Lower Paleolithic traditions. The absence of Levallois debitage and organic soft hammers are often used as arguments, amongst others, in favor of the second hypothesis. Here, we report new supporting data for the use of bone retouchers and pressure flakers in knapping activities. The specimens were found at the Lingjing site, Xuchang County, Henan, in a layer dated between 105 and 125 ka. This discovery emphasizes the importance of combining evidence from a variety of aspects of material culture, including anthropogenically modified faunal remains, in order to accurately define Chinese Paleolithic technological traditions.